Socio-historial and cultural relevance of the journals of Universidad Nacional - Soto-Ramírez, Marybel (2021)
The essay states that journals play a decisive socio-historical and cultural role that contributes to the work of the university as an institution of culture. To this end, it proposes a journey through some of the milestones of the constitution of the scientific periodical press of the National University and elaborates on the historical and pivotal role of the journal as an eminently academic or intellectual practice in the communication of science.